Study on the soil corrosivity towards the buried water supply pipelines in Madhyapur Thimi municipality, Bhaktapur - Dahal, Kumar P; KC, Dinesh; Bhattarai, Jagadeesh (BIBECHANA, 2014)
This research work is carried out to identify the corrosive nature of soils towards the buried-galvanized steel and cast iron pipelines buried in Sanothimi areas of Madhyapur Thimi municipality, Bhaktapur based on different soil parameters such as organic content, moisture content, pH, resistivity, oxidation-reduction potential, chloride and sulfate ions. The soil parameters of the collected soil samples from the study areas were analyzed using standard ASTM methods. Concentrations of these soil parameters measured in this study were found as: organic content (0.9- 7.9%), moisture content (8.0-36.7%), pH (6.8-7.7), resistivity (3900-16700 ohm.cm), oxidation-reduction potential (337-461 mV vs SHE), chloride (25-71 ppm) and sulfate (35-464 ppm) contents. These soil parameters gave an indication of “mildly corrosive” to “less corrosive” nature of soils on the galvanized steels and cast iron pipelines buried in the study areas. Based on the findings of the present studies, it can be advised to the related authorities or local people that simple modification of the soils by using cheapest non-conducting materials like gravel or sand around the buried water supply pipelines before undergrounding them in the study areas is very beneficial from the corrosion point of view to increase their life time. DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10387 BIBECHANA 11(1) (2014) 94-102